Enhancement of wheat productivity through efficient nutrient management practices - Mukherjee, Dhiman (Annals of Agricultural Research, 2018)
A field experiment was conducted during the winter season of 2014 and 2015 at the AB block farmof Bidhan Chandra Krishi Viswavidayalaya, Kalyani, to find out effect of different organic sourceof nutrient along with nitrogen levels with its application time on growth and yield of wheat (Triticumaestivum (L.) emend. Fiori & Paol.). Application of FYM @10 t/ha produced maximum grain (4.12 t/ha) and biological yield (8.93 t/ha), and was at par with FYM @15 t/ha and significantly superior toother treatment of main plot. In subplot treatments, the grain and biological yield of wheat increasedsignificantly with recommended nitrogen application before irrigation (BI), and was at par with thesite specific nutrient management (SSNM) treatment. This treatment recorded 127.1 and 13.4% moregrain and biological yield, respectively over the control. Further, with subplot treatment, moreharvest index noted with the recommended N (BI) and significantly better to other treatments.More benefit: cost ratio registered with the FYM @10 t/ha (1.61) along with the SSNM practice(1.65).